Blue luminescent amorphous carbon nanoparticles synthesized by microplasma processing of folic acid. Issue 1 (22nd September 2017) - Wang, Qingyang; Zhang, Qing; Chen, Yanfei; He, Jie; Jiang, Kai; Hu, Zhigao; Zhong, Xiaoxia
Abstract : Environmentally friendly synthesis of carbon nanoprticles (C‐NPs) from folic acid (FA) is realized with the assistance of microplasma. TEM shows that the synthesized FA C‐NPs are amorphous and of diameter around 47 nm. The produced FA C‐NPs exhibit an excitation independent emission around 445 nm with the fluorescence quantum yield 13% at excitation wavelength of 370 nm. X‐ray photoelectron spectroscopy (XPS) shows the FA C‐NPs are composed of carbon (64.15%), nitrogen (6.04%), and oxygen (29.81%). Raman spectroscopy shows that the intensity ratio between the sp 3 and sp 2 hybridizations of Carbon is 0.35. UV‐Vis absorption, Fourier Transform Infrared Spectroscopy (FTIR), and Nuclear Magnetic Resonance (NMR) spectra provide a deep insight into the fluorescence of FA C‐NPs. With plasma processing of FA, carbon atoms are involved in sp 2 hybridization and amine (NH2 ), NH and COOH groups are converted into ROOCNHCOOR group. As a consequence, the electron donating ability of aromatic ring is enhanced, which plays an important role in the fluorescence of FA C‐NPs. Finally, the promising application of FA C‐NPs in bioimaging is also demonstrated by fluorescence labeling of MCF‐7 cancer cells. Abstract : The folic acid C‐NPs (FA C‐NPs) were synthesized by microplasma processing of folic acide (FA) solution. The produced FA C‐NPs are amorphous and of size diameter around 47 nm, and exhibit an excitation independent emission peak around 445 nm and an enhanced quantum yields (QYs) ranging from 7.1% to 13% depending on excitation wavelength. Cell experiment shows the produced FA C‐NPs can be absorbed by MCF‐7 cancer cells and mark the cells clearly with its fluorescence emission.